Health Literacy and Blood Glucose Level in Transitional Albania - Dika, Qamil; Duli, Marsida; Burazeri, Genc; Toci, Dorina; Brand, Helmut; Toci, Ervin (Frontiers in Public Health, 2020)
Aim: Our aim was to assess the independent association between blood glucose level and health literacy (HL) adjusting for many socio-demographic characteristics and body mass index (BMI) in an adult population in Albania, a transitional country in the South Eastern Europe. Methods: A cross-sectional study was carried out in Tirana in 2012-2014 including a population-based sample of 1154 individuals aged ≥18 years (57% women; mean age: 45.5±16.4 years; response rate: 89%). HL was assessed by use of HLS-EU-Q instrument. Blood glucose level was measured in a fasting state by use of rapid finger stick method. Information on socio-demographic characteristics was collected, and BMI was calculated based on measurement of height and weight in all participants. General Linear Model (GLM) and binary logistic regression were used to assess the independent association of blood glucose level and HL adjusting for all socio-demographic factors and BMI. Results: One-third of participants had pre-diabetes (100-125.9 mg/dl) and further 11% had diabetes (≥126 mg/dl) based on the measured blood glucose level. In fully-adjusted GLM, mean blood glucose level was significantly lower among individuals with excellent HL compared with their counterparts with inadequate HL (99.3 vs. 106.0, respectively). Furthermore, the odds for the presence of diabetes in the group of study participants whose HL was “inadequate” were 2.6 times higher (95%CI=1.3-5.4) compared to those whose HL was “excellent”. individuals with (measured) diabetes exhibited significantly lower HL levels than those without diabetes (fully-adjusted OR[inadequate vs. excellent]=2.6, 95%CI=1.3-5.4). Conclusion: We obtained evidence of a strong and significant inverse relationship between measured blood glucose level and HL, independent of many socio-demographic characteristics and measured BMI in a population-based study in a country of the Western Balkans.